1983
DOI: 10.1073/pnas.80.19.5907
|View full text |Cite
|
Sign up to set email alerts
|

Induction of monocytic differentiation and bone resorption by 1,25-dihydroxyvitamin D3.

Abstract: 1,25-Dihydroxyvitamin D3 [1,25(0H)2D3] stimulates bone resorption in man and other vertebrates, in part, by increasing the number of osteoclasts, the principal resorbing cells of bone. Because osteoclasts are very likely derived from a member(s) of the mononuclear phagocyte family, we determined if 1,25(OH)2D3 promotes maturation of these cells by studying its effects on the human promyelocytic leukemia cell line HL-60. Of the vitamin D3 metabolites tested, only 1,25(OH)2D3, at 10-10 to 10-7 M, induces the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
147
2
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(157 citation statements)
references
References 25 publications
7
147
2
1
Order By: Relevance
“…The effective concentration range of calcitriol for FBPase induction is approximately consistent with those for the inductions of lysozyme in HL-60 [21] and M-I [22] cells, of alkaline phosphatase in ROS17/2 cells [23] and of nitroblue-tetrazolium-reducing capability in U937 cells [24]. The induced enzyme activity is strongly inhibited by AMP, a specific allosteric inhibitor of FBPase, and precipitated with anti-(rat liver FBPase) serum.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The effective concentration range of calcitriol for FBPase induction is approximately consistent with those for the inductions of lysozyme in HL-60 [21] and M-I [22] cells, of alkaline phosphatase in ROS17/2 cells [23] and of nitroblue-tetrazolium-reducing capability in U937 cells [24]. The induced enzyme activity is strongly inhibited by AMP, a specific allosteric inhibitor of FBPase, and precipitated with anti-(rat liver FBPase) serum.…”
Section: Discussionmentioning
confidence: 75%
“…HL-60 cells are induced to differentiate into monocytemacrophages by calcitriol [21,26,271. Like calcitriol, 12-O-tetradecanoyl-phorbol 13-acetate also induces HL-60 cells into monocyte-macrophage differentiation [28 -301.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that it induces differentiation in cells of the mononuclear phagocyte series, including such osteoclast characteristics as multinuclearity, carbonic anhydrase II expression and vitronectin receptors (Abe et al 1983, Bar-Shavit et al 1983, Billecocq et al 1990, Medhora et al 1993. Induction of lacunar bone resorption, however, depends on contact with osteoblastic or bone marrow stromal cells, which also express 1,25(OH) 2 D 3 receptors, and it is not known whether 1,25(OH) 2 D 3 induces osteoclast formation through actions on stromal cells, osteoclastic precursors, or both (Chambers 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The active form of 1,25(OH) 2 D 3 and its analogues have been reported to inhibit cell growth and induce differentiation in both normal and malignant cell types. [38][39][40][41][42] The results of the current study demonstrated a numerical reduction of tumor volume in CAC-8-bearing mice treated with 1,25(OH) 2 D 3 and its analogues (EB1089 and analog V). CAC-8-bearing mice treated with analog V maintained body weight better than other CAC-8-bearing groups.…”
Section: Discussionmentioning
confidence: 96%